Splenogonadal Fusion Discovered by Testicular Torsion - Hmidi, Nahla; Makhlouf, Dorsaf; Laamiri, Rachida; Kechiche, Nahla; Hmida, Badii; Ksia, Amine; Sahnoun, Lasaad; Mekki, Mongi; Belguith, Mohsen; Nouri, Abdellatif (Iranian Journal of Pediatric Surgery, 2020)
Splenogonadal fusion, which is adherence of splenic tissue to gonads, is an uncommon congenital anomaly which mainly affects males. Herein, we report a case of splenogonadal fusion in a 20-month-old boy presenting with acute scrotal pain and inflammation. With the suspicion of left testicular torsion, an emergent left scrotal exploration was carried out. It revealed a necrotic left testicle along with a 360° rotation of the spermatic cord and three accessory structures in the lower pole of the testicle. Histology showed the presence of a splenic tissue. Splenogonadal fusion can present as an acute condition mimicking a testicular torsion. But, one should always bear in mind the possibility of this association. Splenogonadal fusion should be included in differential diagnosis of testicular mass to avoid unnecessary orchidectomy.